2008
DOI: 10.1371/journal.pgen.0040004
|View full text |Cite
|
Sign up to set email alerts
|

Analysis and Application of European Genetic Substructure Using 300 K SNP Information

Abstract: European population genetic substructure was examined in a diverse set of >1,000 individuals of European descent, each genotyped with >300 K SNPs. Both STRUCTURE and principal component analyses (PCA) showed the largest division/principal component (PC) differentiated northern from southern European ancestry. A second PC further separated Italian, Spanish, and Greek individuals from those of Ashkenazi Jewish ancestry as well as distinguishing among northern European populations. In separate analyses of norther… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

29
236
1
1

Year Published

2008
2008
2015
2015

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 231 publications
(270 citation statements)
references
References 38 publications
29
236
1
1
Order By: Relevance
“…A recent study using PCA on GWA data in European samples 5 observed a PC that appeared to be largely because of an inversion at around location 9 Mb on chromosome 8p. This region has been identified earlier 26,27 as containing an inversion, and has LD extending over a 4 Mb region around the inversion in the samples used for this study.…”
Section: Detecting Population Differencesmentioning
confidence: 98%
“…A recent study using PCA on GWA data in European samples 5 observed a PC that appeared to be largely because of an inversion at around location 9 Mb on chromosome 8p. This region has been identified earlier 26,27 as containing an inversion, and has LD extending over a 4 Mb region around the inversion in the samples used for this study.…”
Section: Detecting Population Differencesmentioning
confidence: 98%
“…To discern the ancestry of Europeans or European Americans, multiple sets of AIMs have been established that allow correction for population stratification in association studies using Europeans. [5][6][7] Recently, a great number of genetic association studies on various diseases have been conducted on non-European populations.…”
Section: Introductionmentioning
confidence: 99%
“…1c). However, 6 of these reside within a well-known inversion polymorphism on chromosome 8 16 . We established that all genomewide significant signals in the inversion region are attributable to the inversion, and we confirmed that the inversion is associated with neuroticism in both of our neuroticism datasets, the GPC and the UKB (Online Methods and Supplementary Note).…”
mentioning
confidence: 99%